Performance Properties of Half-bleached Weft Knitted Fabrics Made of 100% Cotton Ring Yarns with Different Parameters - Desalegn Atalie; Gashaw Ashagre (Tekstilec)
Knitted fabrics are distinguished by their outstanding comfort for clothing and for their rapid mass production. Though cotton knitted fabrics can provide better comfort, their physical appearance and service life are affected by many factors, and they have a propensity for pilling, abrasion and snagging. The main goal of this research work was to investigate the effect of yarn parameters on the abrasion, pilling and snagging resistance of half-bleached knitted fabrics. Six knitted fabrics were manufactured from 100% cotton carded ring yarn with a linear density of 21, 25, and 30 tex, with two yarn twist levels for each linear density. Except for yarn linear density and twist, the remaining yarn and machine parameters were constant, including fabric manufacturing. The knitted fabrics were treated using a half-bleach treatment before property evaluation. The results showed that knitted fabric made from a finer count of 21 tex with a higher yarn twist of 920 m−1 had the highest mass loss ratio of 2.12–10.76%, and the lowest abrasion resistance of 89–97.88% between 5,000 to 20000 abrasion cycles. The highest abrasion resistance of 96.4–98.9% (mass loss ratio of 1–3.5%) was recorded for a single jersey knitted fabric made from coarser yarn (30 tex) with the lower twist of 826 m−1. The abrasion resistance of knitted fabrics was significantly affected by the thickness of the fabric, while regression analysis proved that fabric thickness and mass loss ratio had very good correlation, with an adjusted R2 value of 93.8%. The snagging resistance of knitted fabrics increased as yarn twist and fineness increased. Pilling propensity increased as yarn linear density increased and twist decreased. Linear regression results revealed that yarn linear density and twist were highly correlated to abrasion resistance (mass loss method) at an adjusted R2 value of 98.6% or 0.986 after 20,000 rubs.